2022
DOI: 10.1111/nep.14119
|View full text |Cite
|
Sign up to set email alerts
|

Infectious complications in adult patients with idiopathic minimal change nephrotic syndrome undergoing immunosuppressive therapy

Abstract: Background Patients with idiopathic minimal change nephrotic syndrome (MCNS) undergoing immunosuppressive therapy are susceptible to infectious complications. Study specifically focusing on adult population's infectious complications is lacking. Methods We retrospectively collected 101 adult patients with biopsy‐proven idiopathic MCNS and analysed for the infectious complications. Published literatures were also reviewed aiming to evaluate the feasibility of prophylactic antibiotic treatment. Results Infectiou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…A previous study on 101 adult NS patients [5], found that 17 (16.8%) developed infectious complications, mainly pneumonia, cellulitis, fasciitis, and urinary tract infections, primarily caused by Gram-negative bacilli. Notably, three deaths occurred due to mycobacterium tuberculosis pneumonia, pseudomonas aeruginosa infection, and acute hepatitis B are.…”
Section: Introductionmentioning
confidence: 92%
“…A previous study on 101 adult NS patients [5], found that 17 (16.8%) developed infectious complications, mainly pneumonia, cellulitis, fasciitis, and urinary tract infections, primarily caused by Gram-negative bacilli. Notably, three deaths occurred due to mycobacterium tuberculosis pneumonia, pseudomonas aeruginosa infection, and acute hepatitis B are.…”
Section: Introductionmentioning
confidence: 92%
“…Most studies have focused on the response to immunosuppressive treatment in NS, kidney outcomes ( 7–9 ), and mechanisms and prevention of acute kidney injury (AKI) ( 10–13 ), with limited literature on adult NS patients with concurrent TB infection. Hsu et al ( 14 ) observed an incidence rate of infectious complications of 16.8% (17/101) in adult NS patients, primarily pneumonia, cellulitis/fasciitis, and urinary tract infections, with one of the three deaths due to TB pneumonia. In the 5 years following the United Nations High-Level Meeting in 2018, over 7 million people died from TB globally, with an estimated 10.6 million people contracting TB in 2021 ( 2 , 15 ).…”
Section: Introductionmentioning
confidence: 99%